Ready for a Change - Tom Thompson (Journal of Research in Rural Education, 1993)
SheridanHigh School islocated inthe townofSheridan, Oregon. Thetown of2500 sitsabout 20miles westof Salem, thestate capitol. The economy isbased heavily on agriculture, primarily logging. In addition, a federal correctional institute recently opened and employsseveralhundred local people. The high school, grades 9 to12, hasabout 230students. Manyofthe students have lived inSheridan alltheirlives and have parents who were born andraised in Sheridan.